2021
DOI: 10.15585/mmwr.mm7021e1
|View full text |Cite
|
Sign up to set email alerts
|

Mask Use and Ventilation Improvements to Reduce COVID-19 Incidence in Elementary Schools — Georgia, November 16–December 11, 2020

Abstract: On May 21, 2021, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).To meet the educational, physical, social, and emotional needs of children, many U.S. schools opened for in-person learning during fall 2020 by implementing strategies to prevent transmission of SARS-CoV-2, the virus that causes COVID-19 (1,2). To date, there have been no U.S. studies comparing COVID-19 incidence in schools that varied in implementing recommended prevention strategies, including mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 6 publications
3
124
0
3
Order By: Relevance
“…Nonpharmaceutical interventions (NPIs), following the protocol launched by the Department of Education of the Catalonian Government (2), were implemented in the educational setting from the beginning of the school year: hand-washing, mandatory mask use for children older than 5, social distancing, organization of children and teachers into bubble groups whenever possible in order to maintain, as far as possible, the same groups of individuals to facilitate contact tracing, and enhanced ventilation in the classroom by keeping doors and windows open, along with other public health practices, such as screening and quarantine the whole group whenever a positive was detected. In fact, it has been demonstrated that all of these measures are essential to mitigate the transmission of SARS-CoV-2 in schools (3)(4)(5)(6)(7). However, clusters of SARS-CoV-2 infection have been detected in any number of educational centers.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmaceutical interventions (NPIs), following the protocol launched by the Department of Education of the Catalonian Government (2), were implemented in the educational setting from the beginning of the school year: hand-washing, mandatory mask use for children older than 5, social distancing, organization of children and teachers into bubble groups whenever possible in order to maintain, as far as possible, the same groups of individuals to facilitate contact tracing, and enhanced ventilation in the classroom by keeping doors and windows open, along with other public health practices, such as screening and quarantine the whole group whenever a positive was detected. In fact, it has been demonstrated that all of these measures are essential to mitigate the transmission of SARS-CoV-2 in schools (3)(4)(5)(6)(7). However, clusters of SARS-CoV-2 infection have been detected in any number of educational centers.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to reduce long-term risks from this novel virus until we understand them better, as well as reduce the risk of new variants emerging by suppressing transmission. There is now extensive evidence that transmission can be reduced through widespread use of face masks [ 78 , 79 , 80 , 81 ], better ventilation [ 82 ] and air filtration [ 83 ]. Contact tracing and isolation are established and effective methods of reducing transmission.…”
Section: Discussionmentioning
confidence: 99%
“…81,82 Therefore, adequately ventilated classroom environments are important measures to reduce the likelihood of transmission. 80,83,84 Similar to all other interventions within the hierarchy of control (Figure 1, 2), it is important to note that adequate ventilation alone will not eliminate the potential for SARS-CoV-2 transmission, especially related to close, unprotected contact. However, given the importance of indoor air quality for overall health and learning, 85 achieving adequate ventilation in schools is an important investment to support improved health, academic performance and to assist in preventing the spread of several infectious diseases.…”
Section: Recommendations For Hand Hygienementioning
confidence: 99%
“…104 While there are limited studies directly evaluating the effectiveness of NMM use in children, there are several ecological studies evaluating SARS-CoV-2 incidence in schools that have found that mask mandates have been associated with lower incidence of SARS-CoV-2 infections. 83,[105][106][107] However, in the setting of low community transmission, the absence of masks in elementary school was associated with minimal transmission, despite regular class sizes. 108 Potential negative consequences related to masking include impact on communication, impaired facial recognition, or identification, altered interactions (i.e., decreased emotional signaling / visual connection) and physical side effects (e.g., discomfort, irritation).…”
Section: Maskingmentioning
confidence: 99%